PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA KONSEP BPUPKI PADA SISWA KELAS V SD INPRES AWIS - Safrin S Jalal (PEDAGOGIK, 2021)
The purpose of this study was to determine the process of applying a problem-based model and improving social studies learning outcomes on the BPUPKI concept in class V SD Inpres Awis to describe student learning outcomes through the application of a problem-based model to the BPUPKI concept in class V SD Inpres Awis.This research is a type of classroom action research (CAR) with the aim of improving social studies learning outcomes for fifth grade students of SD Inpres Awis. The subjects of this study were the fifth grade students of SD Inpres Awis, with a total of 20 students. This research was conducted in two cycles. The data sources in this classroom action research consist of students, researchers, and teachers as evaluators. Students get data about learning outcomes and student activities in the social studies learning process. To see the level of success of student learning by applying mind mapping learning strategies. Teachers as evaluators and observers. To assess and evaluate researchers in the learning process by applying social studies learning strategies. The technique used in this research is the test technique. The questions used in this research are in the form of a description consisting of 10 questions that have been made.The percentage data obtained in the first cycle shows the number of students who completed as many as 4 students, or 20%, while in the second cycle, the number of students who completed the learning evaluation was as high as 16 students, or 80%. This shows that the application of the problem-based learning model in this study can improve student learning outcomes on the BPUPKI concept.